Notch activation promotes osteoblast mineralization by inhibition of apoptosis. Issue 10 (25th April 2018) - Xu, Ying; Shu, Bing; Tian, Ye; Chelly, Marjorie; Morandi, Massimo M.; Barton, Shane; Shang, Xifu; Dong, Yufeng
Abstract : Notch activator Jagged1 (JAG1) plays a critical role in the regulation of osteoblast differentiation and bone metabolism. In this study, JAG1‐induced osteoblast proliferation, differentiation, and mineralization has been analyzed in primary osteoblasts for up to 7 days. Alkaline phosphatase and Alizarin red staining showed an enhanced osteoblast maturation and mineralization in JAG1 treated cells, as well as higher mRNA levels of late osteoblast differentiation markers. In contrast, Notch inhibitor DAPT and deletion of Runx2 totally blocked JAG1 effects on osteoblast mineralization. Flow cytometry data further showed a significantly higher cell proliferation in early stages of culture at day 3, and lower levels of osteoblast apoptosis in late stages of culture at day 7. More importantly, activation of anti‐apoptotic factor BCL‐2 was enhanced, while pro‐apoptotic factor Caspase3 was reduced in JAG1 treated osteoblasts. Therefore, we conclude that cell mineralization is enhanced via anti‐apoptotic actions of Notch signaling within the osteoblast cells. Abstract : JAG1‐mediated Notch activation induced osteoblast mineralization. This enhanced cell mineralization was modulated through decreased cell apoptosis in a caspase3‐dependent manner.